The collections of Lauraceae in the Herbarium of Henri Van Heurck (AWH) - Rodrigues de Moraes, Pedro Luis (Soc Royal Botan Belgique, 2013)
Background and aims - The collections of Lauraceae in the Van Heurck Herbarium (AWH), which is currently on permanent loan to BR, have remained unknown by most of the specialists and by the general public up until the present. The taxonomic status of its one hundred and forty nine specimens of Lauraceae is here presented.Methods - Standard herbarium taxonomy practices were used in conjunction with the literature available. Specimens from fifty eight different herbaria were studied personally, or by checking their holdings available in the internet, or from digital images received from the curators.Key results - The specimens of Lauraceae from AWH are distributed in twenty four genera and seventy eight species with taxonomic status resolved, excepting for three specimens pertaining to species name of status uncertain (one), or to unresolved determination (two). From them, fifty three specimens are nomenclatural types of any sort, which corroborate the relevance of exsiccates acquired by Van Heurck, even for this relatively small set of specimens for the family. Fifteen lectotypifications and one neotypification of species names are proposed here.
Keywords: Lauraceae; historical collections; nomenclature; taxonomy